FRI0054 Microparticles from Rheumatoid Arthritis Patients Induce Apoptosis and Autophagy in Cultured Endothelial Cells. (15th July 2016) - Barbati, C.; Alessandri, C.; Colasanti, T.; Ceccarelli, F.; Pendolino, M.; Vomero, M.; Sabatinelli, D.; Spinelli, F.R.; Miranda, F.; Valesini, G.; Conti, F.
Abstract : Background: Microparticles (MPs) are small membrane vesicles released by many cell types under physiological conditions or pathological situations. Increased levels of MPs have been reported in patients with autoimmune diseases, such as Rheumatoid Arthritis (RA) (1) which is characterized by an accelerated atherosclerosis. TNF is the main cytokine involved in the pathogenesis of RA and many studies agree on the pro-atherogenic role of TNF in RA patients (2). Furthermore, MPs could have a role in endothelial dysfunction, contributing to atherosclerosis in RA patients. Many studies have also shown that an imbalance of the mechanisms of apoptosis and autophagy seems to be involved in endothelial dysfunction. Objectives: The aim of this study was to analyze total and platelet (PMPs)-, endothelial (EMPs)-, leucocyte (LMPs)-derived MPs in RA patients. Moreover, in vitro studies were performed to estimate the effects of serum RA-MPs on vascular endothelium, before and after three months of treatment with TNF inhibitors (TNFi), with special focus on apoptosis and autophagy pathways. Methods: Twenty RA patients and ten sex and age matched Healthy Controls (HC) were enrolled in this study. Experiments were performed using flow cytometry and western blot techniques according to consensus guidelines. MPs were expressed as MPs/microl; autophagy and apoptosis were expressed as LC3II/beta-actin ratio and percentage of annexin V double positive cells respectively. Results: At baseline the total number of MPs was significantly increased in RA patients compared with HC (p=0.002). Only the EMPs subset was increased in RA patients compared with HC (p=0.017). After three months of treatment with TNFi, either the total number of MPs and the EMPs were significantly decreased compared with baseline (p=0.003 and 0.04 respectively). In vitro studies showed that at baseline serum RA-MPs significantly increased, in a dose-dependent manner, both apoptosis and autophagy levels in the human umbilical vein cell line EA.hy926 (p=0.005 and p=0.02, respectively versus untreated cells). After three months of treatment this effect was not more evident (p>0.05, versus untreated cells for both parameters). Furthermore, co-treating EA.hy926 cells with RA-MPs and 3-methyl-adenine (3-MA), a pharmacological inhibitor of autophagy, induced a significant increase of apoptosis (p=0.007 versus MPs-treated cells without 3-MA). Conclusions: Our data demonstrate that the total number as well as the EMPs are significantly increased in RA patients and their levels significantly decreased after TNFi. Moreover, MPs are able to modulate apoptosis and autophagy in EA.hy926 cells. After three months of treatment with TNFi, MPs decrease their harmful effects. The results with 3-MA suggest a protective role of autophagy on apoptosis induction by RA-MPs on endothelial cells. Therefore, these results confirm the potential contribution of MPs to endothelial dysfunction. References: The role of microparticles in the pathogenesis of rheumatic diseases. Beyer C and Pisetsky DS. Nat. Rev. Rheumatol. 2010; 6:21–9. The role of TNF alpha and IL-1 in rheumatoid arthritis. Feldmann M, Brennan FM, Foxwell BM, Maini RN. Curr Dir Autoimmun. 2001;3:188–99. Disclosure of Interest: None declared